Cost-effectiveness analysis of a community-based colorectal cancer screening program in Shanghai, China - Jiang, Hongli; Zhang, Peng; Gu, Kai; Gong, Yangming; Peng, Peng; Shi, Yan; Ai, Dashan; Chen, Wen; Fu, Chen (Frontiers in Public Health, 2022)
Background: Since 2011, through the Community-Based Colorectal Cancer Screening Program in Shanghai, China (SHcsp), residents aged > 50 years were offered initial colorectal cancer screening using the faecal immunochemical test (FIT) and risk assessment questionnaire (RAQ) for free. Colonoscopy was then recommended for positive results. Objective: To evaluate the cost-effectiveness of the Community-Based Colorectal Cancer Screening Program in Shanghai, China from the payer perspective. Methods: This analysis estimated the long-term cost and effectiveness of the 2014–2016 SHcsp based on real-world follow-up data from the SHcsp database, Shanghai Cancer Registry System, vital statistics from Shanghai Municipal Center for Disease Control and Prevention and inpatient CRC expense data from hospitals. A decision-tree model and Markov model were constructed to simulate the 25-year health outcomes. The screening branch was the cohort with a definite diagnosis of adenoma, advanced adenoma, and CRC. The other branch was residents who were neither screened nor treated until CRC symptoms appeared. A payer prospective was adopted to measure direct costs and effectiveness by life years (LYs) and quality-adjusted life years (QALYs) gained, and were discounted by 3%. Stimulation robustness was tested by one-way sensitivity analysis. Results: Of 1,097,656 residents, 13,250 were diagnosed with adenoma, advanced adenoma, or CRC. Assuming those had not been found through screening, SHcsp resulted in 1,570.1 LYs and 13,984.3 QALYs gained at an extra cost of USD9.96 million. The incremental cost-effectiveness ratio (ICER) was USD6,342.02 per LY and USD712.08 per QALY obtained, far below the threshold of USD59,598 of three-time GDP per capita in Shanghai. Conclusion: The SHcsp was cost-effective than no screening strategy. The results were generalisable to the Chinese population for mass CRC screening.